Project Report on Wireless Digital Information Assistant - ABHILASH, KISHORE T, ANIL and BABU PRASAD (2003)
INTERNAL GUIDE: PAULINE, MVJCE EXTERNAL GUIDE: Y RAJESH, AFFINITY SOFTWARE
Keywords: Wireless Digital Information Assistant